Factores de riesgo y consumo de drogas en estudiantes del nivel secundario en una institución educativa pública de Iquitos 2022 - Rios Rengifo, Stefany Eunice Yumi (2023)
The study was aimed at determining the association between drug use and risk factors in secondary school students of the Mariscal Oscar Benavides Public Educational Institution of Iquitos - 2022. The study was confirmatory, descriptive-relational and cross-sectional design, with a population of 1619 students of third, fourth and fifth grade of high school, and a sample of 310 students, selected in a stratified way by proportional and random allocation, two questionnaires were used to measure the study variables. The results of Spearman's Rho statistical test, at the general objective level, showed that there is a significant association between risk factors and drug use in students (r=0.622, significance 0.000). Regarding risk factors, it was determined that respondents reported a high (33.2%), medium (39.4%) and low (27.4%) level. Regarding drug use, it was determined that the respondents reported a High (20.3%), Medium (34.5%), and Low (45.2%) level. Regarding the specific hypotheses, it was found that there is a significant association between individual risk factors and drug use in students in the study sample (r=0.456, significance 0.002). Finally, it was determined that there is significant association between relational risk factors and drug use in students of the study sample (r=0.402, significance 0.000).